Set2 mediated H3 lysine 36 methylation: regulation of transcription elongation and implications in organismal development. (1st February 2013) - Venkatesh, Swaminathan; Workman, Jerry L.
Abstract Set2 is a RNA polymerase II (RNAPII) associated histone methyltransferase involved in the cotranscriptional methylation of the H3 K36 residue (H3K36me). It is responsible for multiple degrees of methylation (mono‐, di‐, and trimethylation), each of which has a distinct functional consequence. The extent of methylation and its genomic distribution is determined by different factors that coordinate to achieve a functional outcome. In yeast, the Set2‐mediated H3K36me is involved in suppressing histone exchange, preventing hyperacetylation and promoting maintenance of well‐spaced chromatin structure over the coding regions. In metazoans, separation of this enzymatic activity affords greater functional diversity extending beyond the control of transcription elongation to developmental gene regulation. This review focuses on the molecular aspects of the Set2 distribution and function, and discusses the role played by H3 K36 methyl mark in organismal development. WIREs Dev Biol 2013, 2:685–700. doi: 10.1002/wdev.109 For further resources related to this article, please visit the WIREs website.